A DEVELOPMENT FRAMEWORK FOR SOFTWARE SECURITY IN NUCLEAR SAFETY SYSTEMS: INTEGRATING SECURE DEVELOPMENT AND SYSTEM SECURITY ACTIVITIES - JAEKWAN PARK; YONGSUK SUH (Nuclear Engineering and Technology, 2014)
The protection of nuclear safety software is essential in that a failure can result in significant economic loss and physical damage to the public. However, software security has often been ignored in nuclear safety software development. To enforce security considerations, nuclear regulator commission recently issued and revised the security regulations for nuclear computer-based systems. It is a great challenge for nuclear developers to comply with the security requirements. However, there is still no clear software development process regarding security activities. This paper proposes an integrated development process suitable for the secure development requirements and system security requirements described by various regulatory bodies. It provides a three-stage framework with eight security activities as the software development process. Detailed descriptions are useful for software developers and licensees to understand the regulatory requirements and to establish a detailed activity plan for software design and engineering.